2013
DOI: 10.1021/jm400266t
|View full text |Cite
|
Sign up to set email alerts
|

Lead Optimization of a 4-Aminopyridine Benzamide Scaffold To Identify Potent, Selective, and Orally Bioavailable TYK2 Inhibitors

Abstract: Herein we report our lead optimization effort to identify potent, selective, and orally bioavailable TYK2 inhibitors, starting with lead molecule 3. We used structure-based design to discover 2,6-dichloro-4-cyanophenyl and (1R,2R)-2-fluorocyclopropylamide modifications, each of which exhibited improved TYK2 potency and JAK1 and JAK2 selectivity relative to 3. Further optimization eventually led to compound 37 that showed good TYK2 enzyme and interleukin-12 (IL-12) cell potency, as well as acceptable cellular J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 100 publications
1
76
1
Order By: Relevance
“…Despite high expression levels and good solution behavior, this fragment of TYK2 failed to crystallize in its apo-state. Addition of a TYK2-specific ATP-competitive inhibitor (24) to the protein sample enabled crystallization, and we obtained a structure of the pseudokinase-kinase module at a resolution of 2.8 Å (Table S1 and Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
“…Despite high expression levels and good solution behavior, this fragment of TYK2 failed to crystallize in its apo-state. Addition of a TYK2-specific ATP-competitive inhibitor (24) to the protein sample enabled crystallization, and we obtained a structure of the pseudokinase-kinase module at a resolution of 2.8 Å (Table S1 and Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
“…This study suggested that selectivity could be achieved not only by directly targeting sequence differences but also by utilizing the overall discrepancy in P-loop conformation or flexibility. 58 X-ray structures of a C-2 methyl analogue 55 complexed with JAK1 (PDB code: 4EHZ) and JAK2 (PDB code: 4F09) revealed differential protein−ligand interactions between these two isozymes, providing an opportunity for improving selectivity (Figure 23). Structure-based design culminated in the identification of a C-2 hydroxyethyl imidazopyrrolopyridine derivative 56 as a potent JAK1 inhibitor with high selectivity over JAK2.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…Based on lead molecule 60, the authors further explored the SAR, focusing on modifications of the phenyl group and the cyclopropylamide moiety [119]. Compounds 61 and 62 showed improved TYK2 enzyme and cell potency, as well as cellular JAK1 and JAK2 selectivity well above that of 60.…”
Section: Tyk2-selective Inhibitorsmentioning
confidence: 99%